HIV Risk and Prevention Needs Among Young Women in Kibra, Kenya - (:unkn) unknown (My University, 2020)
While HIV infection trends in most groups have been declining, certain population groups including young women globally, and especially those who reside in sub-Saharan Africa (SSA), continue to experience increasing HIV risk. In Kenya, young people aged 15-24 years have been reported to have the highest number of new HIV infections, with young women being twice as likely to be infected as their men counterparts. The rate is even higher among young women residing in urban areas. A review of the literature demonstrates that while studies guided by behavioral theories have yielded results in response to HIV, there is still a persistent disparity in new HIV infections between young men and women in Kenya. In addition, an increasing number of scientists and organizations are calling for a structural approach to HIV research. Guided by postcolonial feminist epistemology and a conceptual framework developed from the theory of gender and power and postcolonial theory, the purpose of this qualitative dissertation study was to explore the HIV risk and prevention needs among young women who reside in Kibra, Nairobi Kenya. Seventy-three young women participated in this study. Data were collected through individual and focus group interviews. Data was managed using MAXQDA where transcripts were analyzed centering young women’s stories. Data was analyzed using thematic analysis. This study reports on young women’s daily lived experiences, how young women experience HIV, and how structural factors including gender norms, ethnicity and poverty intersect to exacerbate HIV risk. Findings in this study show that young women experienced HIV risk through factors such as navigating poverty, gender norms and ethnicity. This study has implications on the critical need to understand gender norms, age, poverty, religion, and ethnicity not just as individual factors impacting young women’s HIV risk in Kibra, but also as intersecting with each other to exacerbate risk.
Keywords: Kibra; Nairobi,Kenya; Nursing; Postcolonial theory; Theory of Gender and Power; Young Women